A Piper nigrum based zinc oxide nanoparticles for anti-arthritic and antioxidant activity - Dwivedi, Shradha Devi; Singh, Deependra; Singh, Manju Rawat (Creative Pharma Assent, 2024)
Background: Zinc oxide nanoparticles (ZnONPs) are among the most effective metallic oxide nanoparticles for biological applications. They have potential anti-inflammatory and anti-oxidant properties, desirable biocompatibility, lower toxicity, and minimal cost. Methodology: Using diverse plant extracts for an ecologically friendly production of metallic nanoparticles is a better choice than conventional chemical synthesis techniques. The present study is decisive on the ZnONPs synthesis from a Piper nigrum extract (Pn-ZnONPs). Morphological characteristics of ZnONPs have been studied using UV-spectroscopy, DLS, SEM, and TEM. Further, it is analyzed for its anti-inflammatory (proteinase, collagenase, lipooxygenase, and elastase) and anti-oxidant properties (DPPH˙, SOD, NO, H2O2, and OH). Results and discussion: Synthesis of nanoparticles has been confirmed via visible spectroscopy with maximum absorbance of 350nm, having particle size and zeta potential of 80 nm and +7.4 mV, respectively. SEM and TEM analysis confirmed the nanoparticle's shape to be spherical and arranged compactly. Further, biogenic nanoparticles show desired anti-inflammatory properties by inhibiting the activity of collagenase (68.72%), elastase (65.16%), lipooxygenase (58.098%), and denaturation of protein (65.36%). It also exhibits the capability to suppress Superoxide radicals (64.87%), DPPH (65.46%), Hydrogen Peroxide (64.89%), Hydroxyl radical (68.45%), and Nitric oxide radicals (71.343%), which are responsible for the pathogenesis of many inflammatory disorders. Conclusion: This suggests that P. nigrum Zinc nanoparticles may be a promising agent in treating various inflammatory disorders, such as cancer, Rheumatoid Arthritis, Psoriasis, and others.